2019
DOI: 10.1177/0969733019840753
|View full text |Cite
|
Sign up to set email alerts
|

Everyday ethical challenges of nurse-physician collaboration

Abstract: Background: Collaboration between physicians and nurses is key to improving patient care. We know very little about collaboration and interdisciplinary practice in African healthcare settings. Research question/aim: The purpose of this study was to explore the ethical challenges of interdisciplinary collaboration in clinical practice and education in Botswana Participants and research context: This qualitative descriptive study was conducted with 39 participants (20 physicians and 19 nurses) who participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…Curricular documents, reviewed as part of this study, showed that the ethics training of the nurses and midwives did not provide knowledge and skills for addressing conflicts relating to treatment decisions and how to respond when moral values conflict. When morality is viewed as a set of “codifiable, impersonally action-guiding within an agent or as a compact set of law-like propositions that explains the behavior of a well-formed moral agent” (p. 8), 23 it fails to acknowledge the social environment in which the agent is situated. Such code-like assumptions (respect for autonomy, beneficence, nonmaleficence, and justice) are the main concepts found in the revised nursing and midwifery curriculum of the Nursing and Midwifery Council of Ghana and the professional Code of Ethics documents without consideration of the context of practice which include gender and socio-economic inequities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curricular documents, reviewed as part of this study, showed that the ethics training of the nurses and midwives did not provide knowledge and skills for addressing conflicts relating to treatment decisions and how to respond when moral values conflict. When morality is viewed as a set of “codifiable, impersonally action-guiding within an agent or as a compact set of law-like propositions that explains the behavior of a well-formed moral agent” (p. 8), 23 it fails to acknowledge the social environment in which the agent is situated. Such code-like assumptions (respect for autonomy, beneficence, nonmaleficence, and justice) are the main concepts found in the revised nursing and midwifery curriculum of the Nursing and Midwifery Council of Ghana and the professional Code of Ethics documents without consideration of the context of practice which include gender and socio-economic inequities.…”
Section: Resultsmentioning
confidence: 99%
“…Under these circumstances, interprofessional collaboration became impossible since it damaged their identity and eroded their sense of responsibility. Similarly, Sabone et al 23 found that physician domination and lack of recognition of nurses' role hindered interprofessional collaboration among nurses and doctors in Botswana.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7/56 empirical studies, all qualitative interview studies, recruited participants internationally with no specific location stated [ 40 , 54 , 55 , 58 , 60 , 63 , 73 ]. Of the remaining studies, all but one were single-country studies: Botswana [ 75 ], Canada [ 41 , 65 ], China [ 57 ], Denmark [ 39 , 43 ], Dominican Republic [ 44 ], Germany [ 51 , 84 ], India [ 61 ], Iran [ 38 , 46 , 49 , 68 , 70 72 , 78 , 82 , 98 ], Italy [ 45 ], Mexico [ 87 ], the Netherlands [ 76 ], New Zealand [ 47 ], Norway [ 42 , 52 , 56 , 64 , 80 , 81 , 83 ], Saudi Arabia [ 34 37 ], Tanzania [ 69 , 74 ], Uganda [ 67 ], UK [ 86 ], and USA [ 50 , 53 , 59 , 62 , 66 , 77 , 79 , 85 , 85 ]. The remaining study was undertaken in both Sierra Leone and the UK [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was also documented in other studies (Sandelowski, 1986;Manning, 2006). A study found that work environment, resources and values regarding a physician-nurse collaboration played a major role in this relationship (Sabone et al, 2019).…”
Section: Physiciannurse Collaborationmentioning
confidence: 99%